Analysis of Factors Affecting Firm Performance Moderated by Competitive Strategies - Caroline Immanuel; Sofia Prima Dewi (Jurnal Akuntansi, 2022)
The purpose of this research was to obtain evidence on the effect of financial leverage and components of intellectual capital (human capital efficiency, structural capital efficiency, capital employed efficiency) on firm performance with competitive strategies as moderation in manufacturing companies listed in Indonesian Stock Exchange during three years. The sample was selected using the cluster sampling method amounted to 27 companies. Data processing methods were performed using EViews. The results showed that financial leverage, human capital efficiency, and structural capital efficiency have an influence on firm performance, while capital employed efficiency and financial leverage moderated by competitive strategies have no influence on firm performance.  Keywords: Financial Leverage; Intellectual Capital; Competitive Strategies; Firm Performance